2018
DOI: 10.1111/rda.13366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of presence or absence of antibiotics and use of modified single layer centrifugation on bacteria in pony stallion semen

Abstract: Contents Bacteria contaminate semen during collection and handling. The objective of this study was to identify the bacteria in pony stallion semen, the effects of antibiotics included in commercial semen extenders (lincomycin and spectinomycin) and the effect of modified single layer centrifugation (MSLC), on bacterial load. Ejaculates from six pony stallions, 3 ejaculates per animal, were extended in EquiPlus extender either with or without antibiotics. Aliquots were processed by MSLC to form four treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
(44 reference statements)
3
19
1
1
Order By: Relevance
“…were isolated from all stallion semen samples, in agreement with most previous studies on fresh semen ( Al-Kass et al., 2019 ; Corona, Cossu, Bertulu & Cherchi, 2006 ; Ortega‐Ferrusola et al., 2009 ; Pasing et al., 2013 ) and even in frozen semen ( Corona & Cherchi, 2009 ; Neto et al., 2015 ). However, in contrast to our previous study on semen from pony stallions in Austria ( Al‐Kass et al., 2018 ), Corynebacterium spp. were detected in only three of the 11 samples in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…were isolated from all stallion semen samples, in agreement with most previous studies on fresh semen ( Al-Kass et al., 2019 ; Corona, Cossu, Bertulu & Cherchi, 2006 ; Ortega‐Ferrusola et al., 2009 ; Pasing et al., 2013 ) and even in frozen semen ( Corona & Cherchi, 2009 ; Neto et al., 2015 ). However, in contrast to our previous study on semen from pony stallions in Austria ( Al‐Kass et al., 2018 ), Corynebacterium spp. were detected in only three of the 11 samples in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The remaining taxa were Staphylococcus and Streptococcus , which are commensals on skin, mucus membranes and the respiratory tract; Kytococcus and Propionobacterium , which are commensals on skin Al‐Kass et al. (2018) ; Neisseria which is a commensal of mucosa ( vetbact website, 2020 ); Mycoplasma which is present in the oral cavity and urogenital tract ( vetbact website, 2020 ); Oligella which is a commensal of the urogenital tract and may cause opportunistic infections ( Roussau et al., 1987 ); Kocuria which are isolated from the human oropharynx ( Al‐Kass et al., 2018 ); and Psychrobacter , which is found in water but has also been isolated occasionally from human beings ( vetbact website, 2020 ). A potential pathogen, Pseudomonas spp., was isolated in low numbers (1 or 2 colony forming units /mL) in three samples ( Blanchard et al., 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SLC was effective in removing 81% to > 90% of bacteria from stallion semen, depending on bacterial load and species [ 80 ]. Similar results were found in a study by Al-Kass et al [ 67 ], although interestingly, they found that 25% of the bacteria remained in the samples after SLC if antibiotics were present in the extender, whereas only 18% of the bacteria remained after SLC where no antibiotics were included. Further studies are underway using a low-density colloid to separate boar spermatozoa from seminal plasma with its bacterial load, without selecting for robust spermatozoa [ 82 ]; this method has not been tested with stallion semen yet.…”
Section: Alternatives To Addition Of Conventional Antibiotics To Semen Extenderssupporting
confidence: 90%
“…Adverse effect on sperm motility and velocity. These authors concluded that the presence of gentamicin could affect sperm function during cooled storage [67] Llincomycin and spectinomycin Sperm DNA fragmentation index was greater in the samples containing these antibiotics than in those without. Sperm motility, membrane integrity and mitochondrial membrane potential were not different between semen samples with and without lincomycin and spectinomycin [64] Potassium penicillin G-amikacin disulfate, ticarcillin disodium-potassium clavulanate, piperacillin sodium/tazobactam sodium, or meropenem Slight differences were detected for sperm motility and kinematics and in chromatin integrity when various antibiotic combinations were used [68] Adding amikacin sulfate and potassium penicillin G to INRA-96 ® extender (already contains penicillin, gentamicin and amphoteracin-B)…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation